Multi-Areas Optimal Reactive Power Flow - Granada, Mauricio E.; Rider, Marcos J.; Mantovani, Jos R. S. [UNESP]; Shahidehpour, Mohammad; IEEE (Ieee, 2008)
This paper describes a method for the decentralized solution of the optimal reactive power flow (ORPF) problem in interconnected power systems. The ORPF model is solved in a decentralized framework, consisting of regions, where the transmission system operator in each area operates its system independently of the other areas, obtaining an optimal coordinated but decentralized solution. The proposed scheme is based on an augmented Lagrangian approach using the auxiliary problem principle (APP). An implementation of an interior point method is described to solve the decoupled problem in each area. The described method is successfully implemented and tested using the IEEEE two area RTS 96 test system. Numerical results comparing the solutions obtained by the traditional and the proposed decentralized methods are presented for validation.
Keywords: Decomposition methods; interior point algorithm; multi-area power systems; optimal reactive power flow; VAR planning